Water hyacinth (Eichhornia crassipes) leaf protein concentrate as soybean protein replacement in Litopenaeus vannamei postlarvae diet - Chavez, Nicole Niña G. (College of Fisheries, University of the Philippines, 2013)
An assessment of the nutritive value of water hyacinth leaf protein concentrate (WHLPC) as a dietary proetin source in formulated diets was carried out in Litopenaeus vannamei postlarvae. Four experimental diets with 0%, 25%, 50%, and 75% of the soybean meal dietary protein replaced by WHLPC, were formulated. All diets were formulated t be isonitrogenous (38% crude protein) and isolipidic (8% crude lipid). Diet containing soybean meal, fishmeal and squid meal as protein sources served as the control. The experimental diets were fed to triplicate groups of shrimp for ten weeks in 30-L aquarium tanks. Results show that growth and overall biological performance of shrimps in terms of SGR, PER, FCE, and survival in treatment receiving the 25% WHLPC replacement is comparable to that of the treatment receiving the full soybean meal diets. Replacement levels beyond 25% tend to elicit significant depression in biological growth performance of the shrimp. Gross carcass composition of the L. vannamei postlarvae was not significantly affected (P>0.05) with increasing levels of WHLPC i the diet. Survival was high among treatments even at the highest WHLPC replacement levels. Digestibility measured in terms of nutrient hydrolysis using midgut gland extract showed that WHLPC is more digestible than both fishmeal and soybean meal dietary ingredients. In conclusion, soybean meal can be substituted with WHLPC to about 25% in the diet of L. vannamei without affecting the overall biolgical performance of the shrimp.